Cometabolism and Gas Chromatography for the Sensitive Detection of Bacteria - Mitruka, B. M. (1969)
Salmonella typhimurium, Escherichia coli, and Staphylococcus aureus were grown in media containing one of several halogenated organic acids which the bacteria metabolized but could not use as a major carbon and energy source for growth. Gas chromatographic techniques were employed to detect the presence of low population densities by analysis for products formed by the microorganisms. By virtue of the presence of the cometabolizable halogenated substrate in the medium, the sensitivity of procedures for detecting the presence of S. typhimurium, E. coli, and S. aureus was increased more than 7,000-, 20,000-, and 1,000-fold, respectively.